Pengaruh Work Engagement, Work-Life Balance, Self-Efficcay, dan Fleksibilitas Jam Kerja Terhadap Kepuasan Kerja Karyawan Cafe black Dew, Pacet - Erissa Putri Maulidiyah; Mohammad Rizal; Satria Putra Utama (E-JRM : Elektronik Jurnal Riset Manajemen, 2026)
Abstract This study aims to analyze the influence of Work Engagement, Work-Life Balance, Self-Efficacy, and Working Hours Flexibility on Employee Job Satisfaction at Black Dew Cafe, Pacet. The research method used is quantitative with an explanatory research approach. The sampling technique used saturated sampling, with a sample of 39 respondents from all employees of Black Dew Cafe. Data were collected through questionnaires and analyzed using multiple linear regression. The results showed that simultaneously, Work Engagement, Work-Life Balance, Self-Efficacy, and Working Hours Flexibility had a positive and significant effect on Job Satisfaction. Partially, Work-Life Balance, Self-Efficacy, and Working Hours Flexibility had a positive and significant effect on Job Satisfaction, while Work Engagement had no significant effect on Job Satisfaction. Keywords: Work Engagement, Work-Life Balance, Self-Efficacy, Working Hours Flexibility, Job Satisfaction